Utilization, perceived benefits and concerns regarding robotic technologies among community pharmacists - Anan S. Jarab; Ahmad Z. Al Meslamani; Walid Al-Qerem; Yazid N. Al Hamarneh; Amal Akour (Future Science OA)
Background Robotic technology is being rapidly adopted worldwide. The purpose of this study was to quantify the prevalence of robotic technology use among UAE community pharmacists, evaluate their perceived benefits and concerns, and identify factors that predict heightened concern levels.Research design and methods The present study utilized a validated self-administered survey, which was distributed in person to community pharmacists in different regions of Abu Dhabi and other Emirates. The questionnaire comprised sociodemographic and job‑related items, an operational definition of robotics, a 5‑point Likert scale on perceived benefits, a 4‑point Likert scale on perceived concerns (recoded to a 0–14 score), and a checklist of potential robotic pharmacy services.Results Pharmacists holding only a bachelor’s degree and pharmacy owners reported higher median concern scores than those with postgraduate degrees and pharmacists in charge, respectively. Additionally, pharmacists without training on robotic systems and those with heavier workloads dispensing ≥30 prescriptions per day or serving ≥10 patients per day also showed significantly greater concerns than their counterparts.Conclusion It is necessary to implement training initiatives aimed at enhancing awareness and understanding of robotic technologies among pharmacists.